The requirements for the application of the Learning Organization at schools applying King Abdullah’s project for the development of public education at Riyadh City - AL-Waheaid, Nahed Mansour; AL-Fantok, Abdulah Abdulrahman (Journal of Educational and Psychological Sciences, 2020)
The study aimed to determine the administrative, organizational, material, technical and human resources requirements, which are required for the implementation of the learning organization in the schools of the project of the Development of Riyadh City from the viewpoint of the female leaders and teachers. The study used the descriptive method in its survey method. The study used a questionnaire that was distributed to the sample of the study which consisted of the schools’ (40) female leaders and (306) female teachers. The study has reached some conclusions: the tool generally obtained an average of (3.70 out of 5). On the level of areas, the administrative and organizational requirements necessary for the application of the educated organization in the schools of the project for the Development of Riyadh city got an arithmetic average (3.69 out of 5.00). The material and technical requirements got an average of (3.53). The human requirements obtained an average of (3.87) and all of them came to a large extent. There were statistically significant differences at the level of significance (0.05) and less between the mean scores of the responses of the items of the study on the administrative and regulatory requirements, with the varying of the variable of nature of the work to the favor of the female leaders, while There were no statistically significant differences between the mean scores of the responses of the items of the study on the other requirements. In the light of the results, a number of recommendations and proposals were presented.